KEBIJAKAN PENDAYAGUNAAN HEMP (Ganja Industri) UNTUK KEPENTINGAN INDUSTRI DI INDONESIA - M. Taufan Perdana Putra (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
ABSTRACT The journal discusses the urgency of legalizing hemp in Indonesia and policy forms utilization of hemp for industrial interests in Indonesia. the approach to this problem can not be separated from policy-oriented approach. Policy approach includes the notion of goal-oriented approach, a rational approach, economical and pragmatic approach and value-oriented approach. The above two problems are obtained answers that hemp urgency in Indonesia is to industry interests which underpins the national economy. Policies utilization of hemp to industry interests in Indonesia Utilization policies for the interests of the hemp industry in Indonesia include the establishment of national regulatory bodies hemp, hemp cultivation regulation of the mechanisms by farmers, the mechanism of regulation of hemp for industrial use by agencies of the mechanisms of export and import settings. Keywords: Utilization of Policy, Hemp, Industri. Â ABSTRAK Jurnal ini membahas tentangÂ  urgensi legalisasi hemp di Indonesia dan bentuk kebijakan pendayagunaan hemp untuk kepentingan industri di Indonesia. Pendekatan yang digunakan terhadap masalah ini tidak dapat terlepas dari pendekatan yang berorientasi pada kebijakan. Pendekatan kebijakan mencakup pengertian pendekatan yang berorientasi pada tujuan, pendekatan yang rasional, pendekatan ekonomis dan pragmatis serta pendekatan yang berorientasi pada nilai. Atas kedua permasalahan tersebut diperoleh jawaban bahwa urgensi hemp di Indonesia adalah untuk kepentingan industri yang menyokong perekonomian nasional. Kebijakan pendayagunaan hemp untuk kepentingan industri di Indonesia meliputi pembentukan badan pengawas hemp nasional, pengaturan tentang mekanisme pembudidayaan hemp oleh petani, pengaturan tentang mekanisme pemanfaatan hemp untuk kepentingan industri oleh instansi dan pengaturan tentang mekanisme eksport import. Kata Kunci: Kebijakan Pendayagunaan, Hemp, Industri.